(untitled) - Hademenos, George J. (New York, 1997)
Fortunately for you, there's Schaum's Outlines. More than 40 million students have trusted Schaum's to help them succeed in the classroom and on exams. Schaum's is the key to faster learning and higher grades in every subject. Each Outline presents all the essential course information in an easy-to-follow, topic-by-topic format. You also get hundreds of examples, solved problems, and practice exercises to test your skills.
Keywords: Biophysics,Physics,Sinh lý học,Vật lý; Outlines, syllabi, etc.,Outlines, syllabi, etc.,Dàn ý, khung chương trình,Dàn ý, khung chương trình